Elisabeta Scurtu, "Familii de preoți greco-catolici din Țara Năsăudului: 1700-1948" (Cluj-Napoca: Mega, 2021) [Families of Greek Catholic priests from the Land of Nasaud (1700-1948)] - BARNA, Daniel Cornel (Studia Universitatis Babeș-Bolyai Historia, 2023)
Elisabeta Scurtu’s professional activity was distinguished by a constant preoccupation for cultural and ecclesiastical history. She was initially a history teacher at the “Logos” High School of Bistrița. Subsequently, she collaborated with the County Center for Culture in Bistrița Năsăud County, and, in the end, she was the assistant counselor of the County Directorate for Culture, Bistrița-Năsăud. Elisabeta Scurtu’s fields of research focus on local history, with an emphasis on cultural and ecclesiastical issues. From a geographical viewpoint, the studies she conducted focused on the historical area called the Land of Nasaud. Thus, Elisabeta Scurtu’s book, entitled Familii de preoți greco-catolici din Țara Năsăudului: 1700-1948 [Families of Greek Catholic priests from the Land of Nasaud (1700-1948)], is a reflection of her long-standing concerns and a well-rounded approach to a topic from her primary field of interest. Given her previous publications that approached cultural and religious matters, her qualification is well-founded and her research endeavour is thus supported by a strong scholarly background.